Você está na página 1de 6

A.

Table of Integrals
1) 2) 3) 4) 5) 6) 7) 8) 9) 10) 11) 12) 13)

dx =

1 n +1 x n +1

x dx = ln x udv = uv - vdu u( x )v( x )dx = u( x )v( x ) - v( x )u( x )dx ax + b dx = a ln(ax + b) ( x + a)2 dx = x + a ( x + a)


dx
n

-1

x a dx = ( x + a)n + , n -1 1 + n 1 + n ( x + a)1+ n (nx + x - a) (n + 2)(n + 1) x


-1 2

n x( x + a) dx =

1 + x 2 = tan
dx xdx 1

-1

a2 + x 2 = a tan

( x / a) + x2 )

a2 + x 2 = 2 ln(a

x 2 dx -1 a2 + x 2 = x - a tan ( x / a) x 3dx 1 2 1 2 2 2 a2 + x 2 = 2 x - 2 a ln(a + x ) 2 ax + b tan -1 2 4 ac - b 2 4 ac - b 2 1 ab

14) ( ax 2 + bx + c)-1 dx = 15) 1

( x + a)( x + b) dx = b - a [ln(a + x ) - ln(b + x )] ,


x 1

16)

( x + a)( x + b) dx = a - b [a ln(a + x ) - b ln(b + x )] ,

ab

Math 351 Spring 2002 California State University, Northridge

2002 B. E. Shapiro Page 537

17) 18) 19) 20) 21) 22) 23)

( x + a)2 dx = a + x + ln(a + x ) ,

ab

x ln( ax 2 + bx + c) b 2 ax + b -1 dx tan = ax 2 + bx + c 2 2a a 4 ac - b 2 4 ac - b 2 3/ 2 x - adx = 3 ( x - a) 1 x a dx = 2 x a 1 a - x dx = 2 a - x 2 3/ 2 2 5/ 2 x x - adx = 3 a( x - a) + 5 ( x - a) 2b 2 x ax + bdx = 3a + 3 b + ax

2b 2 4bx 2 ax 2 24) ( ax + b)3 / 2 dx = b + ax + + 5 5 5a 25) 26) 27)

x 2 dx = ( x 2 a) x a xa 3 x a-x x dx = - x a - x - a tan -1 a-x x-a x dx = x x + a - a ln x+a

x + x+a

]
( )

4b 2 2bx 2 x 2 28) x ax + bdx = 2 + 15a + 5 b + ax 15a 29)

b 2 ln 2 a x + 2 b + ax b x x 3/ 2 x ax + bdx = + b + ax 2 4 a3 / 2 4a

30)

b 2 x bx 3 / 2 x 5 / 2 3/ 2 x ax bdx + = 2 + 12 a + 3 b + ax 8a 8a 1 1 x 2 a 2 dx = x x 2 a 2 a 2 ln x + x 2 a2 2 2 a 2 - x 2 dx = x a2 - x 2 1 1 x a 2 - x 2 - a 2 tan -1 2 2 2 2 x a
Math 351 Spring 2002 California State University, Northridge

b3 ln 2 a x + 2 b + ax
5/ 2

31) 32)

2002 B. E. Shapiro Page 538

1 33) x x 2 a 2 = ( x 2 a 2 )3 / 2 3 1 34) dx = ln x + x 2 a 2 2 2 x a 35) 36) 37) 38)

x a2 - x 2 dx = - tan -1 2 2 x a a2 - x 2 x dx = x 2 - a 2 x 2 a2 x dx = - a 2 - x 2 2 2 a -x 1 x2 x 2 a2 x2 dx = 1 1 x x 2 a 2 m ln x + x 2 a 2 2 2

39)

x a2 - x 2 1 1 dx = - x a - x 2 - a 2 tan -1 2 2 2 2 2 2 x a a -x b x ax 2 + bx + c = ax 2 + bx + c + 4a 2 + 4 ac - b 2 2 ax + b + 2 ax 2 + bc + c 3 / 2 ln a 8a

40)

41)

x 3 bx 8ac - 3b 2 2 2 x ax bx c + + = 3 + 12 a + 2 ax + bx + c 24 a b( 4 ac - b 2 ) 2 ax + b + 2 ax 2 + bc + c ln 5/ 2 a 16 a 1 2 ax + b ln + 2 ax 2 + bx + c a a 1 b 2 ax + b ax 2 + bx + c - 3 / 2 ln + 2 ax 2 + bx + c a a 2a

42) 43)

1 ax + bx + c x ax 2 + bx + c
2

dx = dx =

44) ln xdx = x ln x - x 45) ln( ax + b)dx =

ax + b ln( ax + b) - x a 2b -1 ax tan - 2x b a 2 a -1 bx tan - 2x a b

46) ln( a 2 x 2 b 2 )dx = x ln( a 2 x 2 b 2 ) + 47) ln( a 2 - b 2 x 2 )dx = x ln( a 2 - b 2 x 2 ) +

Math 351 Spring 2002 California State University, Northridge

2002 B. E. Shapiro Page 539

48) ln( ax 2 + bx + c)dx = 49) x ln( ax + b)dx =

2 ax + b b 1 4 ac - b 2 tan -1 - 2x + + x ln ax 2 + bx + c 2a 2 a 4 ac - b

b b2 1 1 x - x 2 + x 2 - 2 ln( ax + b) 2a 4 2 a

a2 1 1 50) x ln( a 2 - b 2 x 2 )dx = - x 2 + x 2 - 2 ln( a 2 - bx 2 ) 2 2 b 51) e ax dx = 52) 1 ax e a 1 i p 2 x -t 2 xe ax + 3 / 2 erf i ax where erf ( x ) = e dt a p 0 2a

xe ax dx =

53) xe x dx = ( x - 1)e x x 1 54) xe ax dx = - 2 e ax a a 55) x 2e x dx = e x ( x 2 - 2 x + 2) x2 2x 2 - 2 + 3 56) x 2e ax dx = e x a a a 57) x 3e x dx = e x ( x 3 - 3 x 2 + 6 x - 6)


1 58) x ne ax dx = ( -1)n G[1 + n, - ax ] where G ( a, x ) = t a -1e - t dt x a
2

59) e ax dx = -i

p erf ix a 2 a

60) sin xdx = - cos x 61) sin 2 xdx = x 1 - sin 2 x 2 4 3 1 62) sin 3 xdx = - cos x + cos 3 x 4 12

63) cos xdx = sin x x 1 + sin 2 x 2 4 3 1 65) cos3 xdx = sin x + sin 3 x 4 12 1 66) sin x cos xdx = - cos2 x 2 64) cos2 xdx =
2002 B. E. Shapiro Page 540
Math 351 Spring 2002 California State University, Northridge

1 1 sin x - sin 3 x 4 12 1 1 68) sin x cos2 xdx = - cos x - cos 3 x 4 12 x 1 69) sin 2 x cos2 xdx = - sin 4 x 8 32 67) sin 2 x cos xdx = 70) tan xdx = - ln cos x 71) tan 2 xdx = - x + tan x

1 72) tan 3 xdx = ln[cos x ] + sec2 x 2 cos( x / 2) + sin( x / 2) 73) sec xdx = ln cos( x / 2) - sin( x / 2) 74) sec2 xdx = tan x 75) sec3 xdx = cos( x / 2) + sin( x / 2) 1 sec x tan x + ln cos( x / 2) - sin( x / 2) 2

76) sec x tan xdx = sec x 1 2 sec x 2 1 78) sec n x tan xdx = secn x , n 77) sec2 x tan xdx = 80) csc2 xdx = - cot x 79) csc xdx = ln tan( x / 2) 1 1 81) csc3 xdx = - cot x csc x - ln(cos( x / 2)sin( x / 2)) 2 2 1 82) csc n x cot xdx = - cscn x , n 0 n 83) sec x csc xdx = ln tan x 84) x cos xdx = cos x + x sin x

n0

85) x 2 cos xdx = 2 x cos x + (2 - x 2 )sin x

1 86) x n cos xdx = - (i )1+ n G (1 + n, -ix ) + ( -1)n G (1 + n, ix ) 2 1 87) x n sin xdx = - (i )n G (n + 1, -ix ) - ( -1)n G (n + 1, -ix ) 2

} }
2002 B. E. Shapiro Page 541

Math 351 Spring 2002 California State University, Northridge

88) e x sin xdx = 89) 90) 91) 92) 93)

1 x e [sin x - cos x ] 2 1 bx bx e sin(ax )dx = b2 + a2 e [b sin ax - a cos ax ] 1 x x xe sin xdx = 2 e [cos x - x cos x + x sin x ] 1 x x e cos xdx = 2 e [sin x + cos x ] 1 bx bx e cos(ax )dx = b2 + a2 e [a sin ax + b cos ax ] 1 x x xe cos xdx = 2 e [ x cos x - sin x + x sin x ]

94) cosh xdx = sinh x e ax 95) e ax cosh bxdx = 2 [a cosh bx - b sinh bx ] a - b2 96) sinh xdx = cosh x e ax 97) e ax sinh bxdx = 2 [- b cosh bx + a sinh bx ] a - b2 98) e x tanh xdx = e x - 2 tan -1(e x ) 99) tanh axdx = 100) 101) 102) 103) 104) 105) 1 ln cosh ax a 1

cos ax cosh bxdx = a2 + b2 [a sin ax cosh bx + b cos ax sinh bx ] cos ax sinh bxdx = a2 + b2 [b cos ax cosh bx + a sin ax sinh bx ] sin ax cosh bxdx = a2 + b2 [- a cos ax cosh bx + b sin ax sinh bx ] sin ax sinh bxdx = a2 + b2 [b cosh bx sin ax - a cos ax sinh bx ] sinh ax cosh axdx = 4a [-2ax + sinh(2ax )] sinh ax cosh bxdx = b2 - a2 [b cosh bx sinh ax - a cosh ax sinh bx ]
1 1 1 1 1

2002 B. E. Shapiro Page 542

Math 351 Spring 2002 California State University, Northridge